Experimental study of Taylor bubble flow in non-Newtonian liquid in a rectangular microchannel. (28th April 2022) - Li, Qingyu; Guo, Wenhao; Li, Hua; Peng, Zhengbiao; Liu, Jingting; Chen, Songying; Liu, Lu; Wang, Lian-Ping; Wang, Guichao
Highlights: Four flow patterns were observed in a gas/ non-Newtonian fluids system. Flow pattern diagrams were drawn for the studied operating conditions. The effect of non-Newtonian viscosity and surface tension on Taylor bubble and liquid slug was studied. The length prediction equations of Taylor bubble/non-Newtonian liquid slug were obtained. Abstract: The flow characteristics of gas and non-Newtonian fluid in a rectangular T-microchannel with cross section of 150 μm × 50 μm are experimentally studied. Four flow patterns are observed, including bubble flow, Taylor flow, transitional flow and annular flow. The effects of two-phase flowrate, the CMC/SDS concentration, and microchannel size on the flow pattern maps and Taylor bubble/liquid slug length are compared. The bubble length increases with gas/liquid flowrates ratio, whilst the change of slug length is opposite. The bubble length decreases with liquid viscosity or surface tension. The slug length increases with the liquid viscosity, but decreases with surface tension. Experimental data is analyzed in relationship to JG /JL, Re and Ca using dimensional analysis. Two empirical equations are given respectively to predict the Taylor bubble/slug lengths. Predictions are largely consistent with the experimental results with maximum 25% variance. This provides an important reference for the controllable operation of two-phase flow in rectangular microchannels.